Vitamin D Deficiency and Immune Disorders in Combined Endocrine Pathology - Komisarenko, Yuliia I.; Bobryk, Maryna I. (Frontiers in Endocrinology, 2018)
Introduction: Combined endocrine pathology is a serious healthcare problem in Ukraine. This prospective study assessed the blood levels of 25-hydroxyvitamin D [25(OH)D] and markers of immune function in response to vitamin D intervention in patients with type 1 and type 2 diabetes mellitus (T1DM and T2DM, respectively) and autoimmune thyroiditis (AIT). Objective: This study evaluated the relationship between the metabolic and immune status of DM + AIT patients with respect to their vitamin D status and changes after vitamin D3 supplementation. Material and Methods: Patients with type 1 or type 2 DM in combination with AIT and decreased circulating levels of 25(OH)D were divided into two groups of 30 patients each. All patients with AIT were euthyroid and receiving hormonal replacement therapy. The levels of carbohydrate and fat metabolism markers, Immunologic markers, namely, Th1-type cytokines (interferon (IFN)-, tumor necrosis factor (TNF)-, interleukin (IL)-2, IL-6, IL-12), Th2-type cytokines (IL-4, IL-5), IL-10, and IL-17 were measured before and after vitamin D3 supplementation. The vitamin D status was assessed according to the level of 25(OH)D. Results: Patients with combined endocrine disorders (DM and AIT) with a decreased vitamin D status had significantly increased background concentrations of Th1-type cytokines and reduced concentrations of Th2-type cytokines (IL-4 and IL-5), IL-10, and IL-17. The results of our study showed that vitamin D3 supplementation in patients with T1DM and T2DM reduced the concentrations of the inflammatory Th1-type cytokines and increased the levels of Th2-type cytokines. Conclusion: The presence of two endocrine diseases, aggravated by decreased circulating levels of 25(OH)D, leads to disorders wherein the immune status is markedly changed. These decreased levels of 25(OH)D contribute to an autoimmune inflammatory process and to the progression of complications in addition to the metabolic disorders. A vitamin D intervention resulted in significant changes in the blood levels of 25(OH)D that are related to parameters of autoimmunity and glucose metabolism. Vitamin D3 supplementation should be considered for the prevention and treatment of combined endocrine pathology. Keywords. Diabetes mellitus, autoimmune thyroiditis, 25-OH D, vitamin D3 supplementation, immune disorders, cytokine profile, Chernobyl disaster